PERANCANGAN SISTEM INFORMASI RESERVASI ONLINE PADA HOTEL VICTORY - Widja Yanto Widja Yanto; Ade Agung Kurniawan; Ichsandi; Lily Indria; Siti Nurlaila (Hira Institute, 2024)
The processing of reservation data at Hotel Victoria still uses the recording in the agenda book so as to experience obstacles - barriers include frequent redundancies, stacking of agenda books that require a lot of places, and the long time it takes to process the search data. In this case, the author designed by using the waterfall method, which uses an object-oriented drawing approach using use case diagrams, activity diagrams, and class diagrams. The author intended a reservation information system based on the web. In making the reservation information system based on the web in order to improve the effectiveness of work in web-based reservation data processing at Hotel Victory